Strong Ties versus Weak Ties in Word-of-Mouth Marketing. Issue 4 (October 2019) - Hu, Hai-hua; Wang, Le; Jiang, Lining; Yang, Wei
It is widely accepted in word-of-mouth (WOM) research that weak ties have a greater macro-level impact than strong ties on the spread of WOM and that marketers should thus intentionally stimulate WOM between weak ties to optimize a given WOM campaign. Here, we challenge this idea based on the fact that, in practice, marketers often incorporate a WOM campaign into other forms of marketing activities, typically advertising. Using an agent-based modeling approach, we demonstrate that while advertising serves as one source of information flow, the WOM that is most effective at driving product growth is created by strong rather than weak ties. The rationale behind this is simple: advertising competes against weak ties in disseminating information globally, and it is this global reach that has been widely considered the vital strength of weak ties over strong ties.